Speech fluency and accuracy as indicators of academic speaking proficiency - Setyawan, Sunoko; Dewangga, Vigo; Pudyastuti, Zusana E. (Journal of English in Academic and Professional Communication, 2026)
Previous studies on the assessment of academic speaking skills in English as a Foreign Language (EFL) context have predominantly emphasized fluency and accuracy as key performance criteria, yet limited attention has been given to empirically examining their suitability as indicators of overall academic speaking proficiency, particularly at the university level. Addressing this gap, the present study aims to investigate the extent to which fluency and accuracy function as key indicators in assessing university-level EFL students’ academic speaking proficiency. A quantitative research method with a correlational design was employed, involving 60 students enrolled in an Academic Speaking course who were selected using purposive sampling. Data were collected through recordings of academic presentation tasks and analyzed using an assessment rubric based on the Common European Framework of Reference (CEFR). The results revealed a significant positive correlation between levels of fluency and accuracy and overall academic speaking proficiency scores. These findings provide empirical evidence of the suitability of fluency and accuracy as indicators in academic speaking assessment. The study highlights the importance of integrating assessment rubrics that place greater emphasis on fluency and accuracy in the teaching and evaluation of academic speaking skills.